THE EFFECT OF PERCEIVED INTERACTIVITY ON PURCHASE INTENTION THROUGH IMMERSIVE EXPERIENCE AMONG TIKTOK LIVE USERS IN MAKASSAR CITY - Sitti Hasbiah; Ilma Wulansari Hasdiansa (Universitas Negeri Makassar, 2026)
Abstract: The rapid growth of live commerce has transformed consumer shopping behavior in digital environments, particularly through social media platforms such as TikTok Live. Interactive communication and immersive shopping experiences are considered important factors influencing consumers’ purchasing behavior during live streaming activities. This study aims to examine the effect of perceived interactivity on purchase intention through immersive experience among TikTok Live users in Makassar City. A quantitative approach was employed using a survey method involving 90 respondents who had previously purchased products through TikTok Live. The sampling technique used was purposive sampling, while data analysis was conducted using Structural Equation Modeling (SEM) with AMOS 22.0. The findings reveal that perceived interactivity positively and significantly affects immersive experience and purchase intention. In addition, immersive experience also has a positive and significant effect on purchase intention. The mediation analysis further demonstrates that immersive experience significantly mediates the relationship between perceived interactivity and purchase intention. These findings indicate that interactive communication and engaging live streaming experiences play an important role in increasing consumers’ willingness to purchase products through TikTok Live. This study contributes to the development of consumer behavior literature in the context of live commerce and provides practical insights for businesses utilizing TikTok Live as a digital marketing platform.Keywords: Immersive Experience, Live Commerce, Perceived Interactivity, Purchase Intention, Tiktok Live.